Coronavirus disease 2019 (Covid-19) outcomes in patients with sarcopenia: A meta-analysis and meta-regression. (April 2022) - Siahaan, Yusak Mangara Tua; Hartoyo, Vinson; Hariyanto, Timotius Ivan; Kurniawan, Andree
Summary: Background: Sarcopenia has been associated with patients' poor quality of life, disability, and hospitalization. As of today, evidence that highlights the association between sarcopenia and Covid-19 outcomes remains unclear. This study sought to analyze whether patients with sarcopenia are at higher risk for developing poor Covid-19 outcomes. Methods: Using specific keywords, we comprehensively go through the potential articles on medRxiv, Europe PMC, and PubMed sources until July 31st, 2021. All published studies on sarcopenia and coronavirus disease 2019 were collected. We were using Review Manager 5.4 and Comprehensive Meta-Analysis 3 software to conduct statistical analysis. Results: There were 9 studies with 492, 245 Covid-19 patients included in the analysis. Evaluation of the data gathered yielded an association between sarcopenia and increased severity of Covid-19 (OR 1.99; 95%CI: 1.37–2.90, p  = 0.0003, I 2  = 79%, random-effect modelling); and mortality from Covid-19 (OR 1.96; 95%CI: 1.11–3.46, p  = 0.020, I 2  = 49%, random-effect modelling). The increased risk of developing severe Covid-19 in a sarcopenic patient is also further influenced by cancer. Conclusions: This study proposes that patients with sarcopenia are at risk of developing poor Covid-19 outcomes. Patients with sarcopenia need special attention and should be prioritized to receive the SARS-CoV-2 vaccine. Registration details: PROSPERO (CRD42021270725). Highlights: Currently, the evidence regarding sarcopenia and Covid-19 outcome is still unclear. Sarcopenia is associated with higher severity and mortality from Covid-19. Patients with sarcopenia should be prioritized to receive SARS-CoV-2 vaccine.